Evaluation of Philips Group split through financial analysis tools - Larionova, Ksenia (2017)
This thesis aimed to examine methods used to evaluate multinational and diversified firms and then use these methods to study the Philips Group and its decision to spin-off of the Philips Lighting sector. Although numerous methods and parameters used to analyze firms already exist, they remain very limited for multinational and diversified firms such as Philips Group or General Electric. In this thesis, hypotheses were based on the theory of the firm and tested using analysis of leverage, profitability and efficiency ratios. This study shows the difficulty of analysing multinational diversified firms caused by a very limited availability of data set. Thus, despite of a great number of ratios described in the literature, only a small portion can be in fact computed using publicly available data. Hypotheses were based on the the paper developed by Chen and Guo (2005). First hypothesis, based on the analysis of capital constraint was attempted, secondly the pace and directions of individual sectors were analysed using profitability and efficiency ratios and thirdly the stock performance was observed. All of this in order to examine whether the motive of the split was to increase the stock prices. It was found that Philips Group nor its Lighting sector did not experience capital constraints, nevertheless an important degree of underperformance amidst analysed figures was found, which suggested that Philips Lighting division was not as good in creating value for shareholders as the HealthTech division was. Moreover, the decision of Philips Group to concentrate on its HealthTech business was positively accepted on stock markets confirming the third hypothesis.